EFFORTS TO INCREASE UNDERSTANDING OF STUDENT PHYSICAL CONCEPTS THROUGH PHET SIMULATION LEARNING MEDIA - Ferawati Artauli Hasibuan; Jainal Abidin (Universitas Negeri Medan, 2019)
The research had done in sixth (VI) semester students of Physics Education Program, Faculty of Teacher Training and Education, University of Graha Nusantara Padangsidimpuan 2018/2019 Academic Year, the total is 20 people. Researchers applied PhET Simulation Interactive based learning by using komputers on modern physics material. The type of research is Classroom Action Research that conducted in three cycles. The purpose of this study was to find out the increasing of understanding student concepts through the application of PhET-based learning media, due to the learning of Modern Physics and it was hoped that students would be able to follow the development of knowledge and technology, one of them is nanotechnology. The learning media that used in this study are Lesson Plan (RPP), Instruments, student activity observation sheets, and observation sheets of the lecturers’ ability to manage learning.The results showed that the application of PhET simulation learning media in physics learning was effective in increasing the understanding of physics concepts of modern physics subject students increasing in each cycle. In the first cycle, the ability to understand the concepts of student physics is still very low with a percentage of 45%, the learning method is still centered on the lecturer, and the response of students to subjects is low. After applying the PhET simulation in cycle II, the understanding of students 'physics concepts increased to 65%, the level of lecturer management in learning was 69.23%, and the students' response was positive in learning. In cycle III, the learning objectives are achieved with a level of understanding the concepts of physics by 85%, pengeloalan lecturers in the classroom by 84.6%, and learning increasingly attract the attention of students. It can be concluded that the PhET simulation learning media in physics learning is very effective to improve student activity in modern physics subject matter of photoelectric effects. The practicality of animation media using simulations can be seen from the students' responses to the implementation of learning using the PhET simulation media for the photoelectric effect results of the development of material / content, linguistic, presentation and graphic aspects. Students are increasingly interested because it is easier and helped to learn through PhET simulation media. The application of PhET simulation learning media in physics learning contributes effectively to lecturers to develop professionalism in managing learning.